Performance of cellular network embedded in the cell edge with vertical coverage by co-frequency - HUJin-kang Z; ENGNa D; HAOMing Z (Tongxin xuebao)
A new hybrid cellular network structure is proposed,where the small base stations equipped with the downward vertical coverage of antenna beam are embedded in the cell edge of current cellular using the same frequency,thereby suppressing the inter-cell interference and improving the signal to interference ratio in the cell edge.Specifically,the radio coverage of these small stations is called vertical coverage,and the coverage of current cellular is called horizontal coverage.Since the proposed network structure does not modify the current cellular network infrastructure,it is easy to operate and implement.The cell interference depth and the interference characteristics in the horizontal coverage and the vertical coverage,as well as their spectral efficiencies are analyzed respectively.Then,the spectral efficiencies of the cell center and the cell edge with vertical coverage are investigated concerning on the proposed new hybrid cellular network structure.The results show that the new hybrid cellular network structure proposed can suppress inter-cell interference and improve cell-edge performance effectively,while achieving higher spectral efficiency.